The cryosphere: an early indicator and global player - Grassl, Hartmut (Polar Research, 1999)
Ice at or below the surface of the planet Earth is an important part of the climate system. The solid phase of water has two unique characteristics which make it both an early indicator of climate change and a global player. First, if warmed to the melting point at 0°C, higher air temperatures and/or higher long-wave back radiation just increase the melting rate but not - as with all other surfaces- the temperature, which stays at 0°C. Small icecaps and mountain glaciers thus become early indicators of a changed climate. Second. If seawater is cooled to the freezing point at about- 1.8"C. the sea ice formation process ejects salt causing the denser water to sink, thereby filling the global ocean interior with very cold water. The location where most of this deep convection occurs is strongly dependent on the freshwater balance and thus on the average salinity of ocean basins. Present ocean configuration and ocean topography, as well as precipitation distribution, make the northern North Atlantic more saline than any other high latitude ocean part and thus the site with most of this deep water formation. Sea ice formation is therefore of high significance for the European climate. Since it drives the near surface warm North Atlantic current northward off the European coast in compensation for southward deep water flow in the western Atlantic, northwestern Europe is warmer by about 4°C than the same latitudes on the eastern Pacific coast of America.
Keywords: Antarktis; isbreer; klimaendringer; kryosfæren; polarområdene; sjøvann; vann

Impact of recent climate on glacier mass balance : studies on Kongsvegen, Svalbard and Jutulstraumen, Antarctica - Melvold, Kjetil (University of Oslo, 1999)
Publication Title: Department of physical geography
Keywords: Antarktis; akkumulasjon; geografi; glasiologi; isbreer